QFD for selecting key success factors in the implementation of quality 4.0. (25th May 2022) - Dror, Shuki
Abstract: Industry 4.0 technological advancements over the last few years have generated a variety of interchangeable methods for achieving quality objectives. The present study seeks to create a framework that will facilitate the selection of key success factors in the implementation of Quality 4.0. Since the ways in which Quality 4.0 technologies can interact present a new industrial reality, our prioritization program addresses the synergy that can exist between technologies. The current study presents the development of a Quality Function Deployment (QFD) methodology for the effective implementation of Quality 4.0. The methodology extracts the desired improvements in quality objectives and translates them into the important Quality 4.0 technologies and, ultimately, into core implementation barriers that need to be reduced, ranked by importance. Normalized improvement scores were calculated at each of three hierarchical levels: quality objectives, Quality 4.0 technologies, and implementation barriers. The components to be improved at each level were selected using the Mean Square Error (MSE) criterion. The methodology was implemented in a food processing company. The vital few quality objectives to be improved were found to be stable quality, equipment reliability, customer satisfaction, and product related complaints. The most important technologies to be considered are big data, enabling technologies, statistics and data mining, and artificial intelligence. Concerns regarding cyber security and outdated systems/infrastructure are the most significant barriers to Quality 4.0 implementation.